The Carcass and Nutritional Meat Characteristics of Sapudi and Cross Merino Sheep - Himmatul Khasanah; Gayuh Syaikhullah; Muhammad Adhyatma (Faculty of Animal Science, Universitas Gadjah Mada, 2022)
Sheep meat plays an important role in accomplishing balanced and healthy nutrition as a source of protein, fat, and essential micronutrients such as zinc, iron, and vitamin B12. The amino and fatty acid composition of meat in different breeds need to be assessed to characterize and determine the development prospects of sheep that produce healthy and good quality meat. Therefore, this study aimed to investigate the phenotypic characteristics of the Sapudi and Cross Merino meat sheep including the carcass performance and meat qualities. We reared four Sapudi and four Cross Merino ewes in the same feed and environmental management for two months then slaughtered and analysed the carcass, non-carcasses and chemical meat properties. We used Bicep femoris muscle to perform proximate, amino acid, and fatty acid contents. An independent t-test was conducted to compared obtained data. Heart weight and protein content were higher in Sapudi sheep. Of the 51 fatty acids observed, we found 11 and 10 types of fatty acid in the Sapudi and Cross Merino meat, respectively. The fatty acid percentage of Sapudi meat tended to have higher value compared to Cross Merino. We also found that the two breeds have the same amino and fatty acid compositions. The levels of glycine, arginine, serine, tyrosine, phenylalanine, lysine and threonine were statistically higher in Cross Merino than Sapudi. In conclusion, the non-carcass, crude protein, amino acid and fatty acid level were significantly different between Sapudi and Cross Merino